Political writings - Spencer, Herbert 1820-1903 (Cambridge University Press, 1994)
This book places Spencer's famous argument for political individualism in his The Man versus the State alongside his early The Proper Sphere of Government, out of which, after due gestation, emerged not only The Man versus the State but also Social Status and his all-embracing theory of evolution. Both are valuable as unyielding statements of anti-state political theory and as sources of perceptive comments on political events of the times. An introduction sets them in their context and examines their main themes. The book will be of interest to both undergraduates and specialists in politics, political theory, social policy, sociology and history
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: State, The; Individualism; Staat; Politik; Individualismus; Bürger